Visual-PSNR measure of image quality - Tanchenko, Alexander (Journal of visual communication and image representation, 2014)
•Objective image quality measure (VPSNR) is developed.•VPSNR has good correlation with MOS for compressed images.•VPSNR can be calculated in the spatial domain.•VPSNR coincides with PSNR on conner cases. Objective assessment of image quality is important in numerous image and video processing applications. Many objective measures of image quality have been developed for this purpose, of which peak signal-to-noise ratio PSNR is one of the simplest and commonly used. However, it sometimes does not match well with objective mean opinion scores (MOS). This paper presents a novel objective full-reference measure of image quality (VPSNR), which is a modified PSNR measure. It will be shown that VPSNR takes into account some features of the human visual system (HVS). The performance of VPSNR is validated using a data set of four image databases, and in this article it is shown that for images compressed by block-based compression algorithms (like JPEG) the proposed measure in the pixel domain matches well with MOS.